2017
DOI: 10.1177/2325967117742077
|View full text |Cite
|
Sign up to set email alerts
|

Platelet-Rich Plasma Injection With Percutaneous Needling for Recalcitrant Lateral Epicondylitis: Comparison of Tenotomy and Fenestration Techniques

Abstract: Background:Recalcitrant lateral epicondylitis (LE) is a common debilitating condition, with numerous treatment options of varying success. An injection of platelet-rich plasma (PRP) has been shown to improve LE, although it is unclear whether the method of needling used in conjunction with a PRP injection is of clinical importance.Purpose:To determine whether percutaneous needle tenotomy is superior to percutaneous needle fenestration when each is combined with a PRP injection for the treatment of recalcitrant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
13
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 57 publications
(110 reference statements)
3
13
0
Order By: Relevance
“…Lim et al reported that needling when combined with PRP injection gives favorable results versus physiotherapy in pain scores, modified Mayo Clinical Performance scores, and even in MRI imaging [ 36 ]. Similarly, beneficial results of PRP injections and concomitant needling were also reported by Gaspar et al Interestingly, this paper reports sustained good outcomes with PRP at a mean follow-up of over 3 years [ 37 ].…”
Section: Lateral Epicondylitissupporting
confidence: 70%
“…Lim et al reported that needling when combined with PRP injection gives favorable results versus physiotherapy in pain scores, modified Mayo Clinical Performance scores, and even in MRI imaging [ 36 ]. Similarly, beneficial results of PRP injections and concomitant needling were also reported by Gaspar et al Interestingly, this paper reports sustained good outcomes with PRP at a mean follow-up of over 3 years [ 37 ].…”
Section: Lateral Epicondylitissupporting
confidence: 70%
“…Both procedures were recently compared. 18 Although the results are similar, increased reduction in long-term pain was observed in the tenotomy group, and more patients required open surgery in the needle tenotomy group. In our study, we performed 15-25 needle passes with periosteum abrasion in the first intervention but only approximately 10 needle passes in the second intervention.…”
Section: Discussionmentioning
confidence: 77%
“…Going deeper, other authors described two different needle tenotomy modalities, including the so‐called peppering technique, which involves less tendon fenestrations (approximately five needle passes), and a more aggressive needle tenotomy involving multiple abrasions until tissue softening. Both procedures were recently compared . Although the results are similar, increased reduction in long‐term pain was observed in the tenotomy group, and more patients required open surgery in the needle tenotomy group.…”
Section: Discussionmentioning
confidence: 99%
“…A study on the long-term efficacy of ATI treatment with a follow-up period of more than 4 years, reports symptomatic and functional improvement without adverse effects, complications, or infections in >70% participants. However, ATI treatment is still being explored with animal studies and preclinical trials, and requires further researches with a larger study population to determine the efficacy and safety ( Table 1 ) [ 22 , 26 , 28 - 34 ].…”
Section: Current Updates On Interventional Therapy With Injectionmentioning
confidence: 99%